Development and Evaluation of the Clinician-Rated Humility Scale - Bell, Chance A. (Journal of psychology and theology, 2022)
Humility is a key virtue in most religious traditions, and empirical evidence links it with healthy religious leader development. Psychological evaluation often forms part of the vocational discernment process for religious leaders. We evaluated development of the clinician-rated humility scale (CRHS) within the clergy candidate psychological evaluation context at a community mental health center in the United States. In Study 1, we examined inter-rater reliability of the CRHS using three methods across 10 calibration tests with clergy candidates (female = 1, male = 9; average age = 34.6 years). Combined convenience and comprehensiveness provided the best method for obtaining the highest agreement. In Study 2, we evaluated the internal and external factor structure of the CRHS using clergy candidates (n = 70) receiving psychological testing (29% female, 70% male; average age = 34.5 years). A final six-item version of the scale showed acceptable model fit, with evidence of a unidimensional factor structure, good internal consistency, and theoretically consistent associations with correlates. The results suggested the CRHS tapped dimensions of caring for others, openness toward personal beliefs, and self-growth. This observer-rated humility scale holds potential in conjunction with self-report measures for use in clinical assessment and research on client humility.